'People like me don't get support': Autistic adults' experiences of support and treatment for mental health difficulties, self-injury and suicidality. (August 2019) - Camm-Crosbie, Louise; Bradley, Louise; Shaw, Rebecca; Baron-Cohen, Simon; Cassidy, Sarah
Autistic people are at high risk of mental health problems, self-injury and suicidality. However, no studies have explored autistic peoples' experiences of treatment and support for these difficulties. In partnership with a steering group of autistic adults, an online survey was developed to explore these individuals' experiences of treatment and support for mental health problems, self-injury and suicidality for the first time. A total of 200 autistic adults (122 females, 77 males and 1 unreported) aged 18–67 (mean = 38.9 years, standard deviation = 11.5), without co-occurring intellectual disability, completed the online survey. Thematic analysis of open-ended questions resulted in an overarching theme that individually tailored treatment and support was both beneficial and desirable, which consisted of three underlying themes: (1) difficulties in accessing treatment and support; (2) lack of understanding and knowledge of autistic people with co-occurring mental health difficulties and (3) appropriate treatment and support, or lack of, impacted autistic people's well-being and likelihood of seeing suicide as their future. Findings demonstrate an urgent need for autism treatment pathways in mental health services.